The Eclipses Abacus, the mechanical predictor of the solar and lunar eclipses. (June 2019) - Popkonstantinović, Branislav; Miladinović, Ljubomir; Obradović, Ratko; Jeli, Zorana; Stojićević, Miša
This paper exposes and explains the synthesis of a mechanism, the Eclipses Abacus, by which the date of solar and lunar eclipses can be predicted and determined sufficiently accurately. Moreover, a three-dimensional (3D) model of this mechanical device is created by using Solid Works application and the simulation of its operation is accomplished by which the accuracy of its predictions can be demonstrated and inspected. This work is significant mainly for education in the field of 3D modeling, mechanism synthesis, and simulation. Moreover, the Eclipses Abacus is interesting for teaching courses in astronomy since it can demonstrate solar and lunar eclipses simply and clearly.